The meister of Decimen City - Raney, Brenna (Camcat Books, 2023)
Supergenius and quasi-villain Rex normally can't go a week without accidentally endangering Decimen City with her science shenanigans. It's been two weeks since her genetically engineered dinosaurs rampaged through town--a good streak for her--but the peace is broken when actual villain Last Dance sets his sights on Decimen. And he wants Rex's help. Before Rex can say "I didn't do it," superheroes who've dragged her to jail on her worst days are crowding her lab to conscript her into quasi-herodom. Rex would rather stay out of it and deal with the dinosaurs that keep calling her Mom, but she can't ignore that she was somewhat responsible for Last Dance's villainy. She'd kept a very disorganized lab. And he was such a nosy brother. She failed to help him back then, but maybe if she stops him now--and keeps the heroes fooled--she can finally set things right. -- Back cover.